PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) BERBANTUAN VIDEO ANIMASI TERHADAP KEMANDIRIAN DAN PEMAHAMAN SISWA SMAN 1 SRESEH - Utami, Elmy Noviyaning; Huda, Nuril; Tobing, Victor Maruli Tua L. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In general, this research aims to determine the effect of the problem based learning (PBL) learning model assisted by animated videos on students' independence and understanding of the mathematics subject of enumeration rules in class XII SMAN 1 Sreseh. This research is quantitative research using Quasi Experimental Design. The population in this study was class XII-1 with 26 students and XII-2 with 27 students. In proving and analyzing this, data collection uses non-test instruments in the form of questionnaires while the test instruments are in the form of questions. Meanwhile, the data analysis tests used are validity, reliability, normality test, homogeneity test, independent sample t-test. The research results are based on hypothesis testing using the help of the IBM SPSS v.21 application, namely the first hypothesis obtained a sig value. 0.000 < 0.05 using the independent sample t-test, there is a significant influence on the use of the problem based learning (PBL) learning model assisted by animated videos on students' learning independence in mathematics subjects with enumeration rules material in class XII of SMAN 1 Sreseh Sampang. The second hypothesis is based on the results of hypothesis testing, a sig value can be obtained. 0.000 < 0.05 using the independent sample t-test, there is a significant influence on the use of the problem based learning (PBL) learning model assisted by animated videos on students' learning understanding in the mathematics subject of enumeration rules in class XII SMAN 1 Sreseh Sampang. So it is more effective to use the problem based learning (PBL) learning model assisted by animated videos on learning independence and students' learning understanding in mathematics subjects, enumeration rules material in class XII SMAN 1 Sreseh Sampang.